From the Halls of Congress to K Street: Government Experience and its Value for Lobbying. Issue 4 (16th July 2019) - Ban, Pamela; Palmer, Maxwell; Schneer, Benjamin
Abstract : Lobbying presents an attractive postcongressional career, with some former congressional members and staffers transitioning to lucrative lobbying careers. Precisely why congressional experience is valued is a matter of ongoing debate. Building on research positing a relationship between political uncertainty and demand for lobbyists, we examine conditions under which lobbyists with past congressional experience prove most valuable. To assess lobbyist earnings, we develop a new measure, Lobbyist Value Added, that reflects the marginal contribution of each lobbyist on a contract, and show that previous measures understate the value of high‐performing lobbyists. We find that former staffers earn revenues above their peers during times of uncertainty, and former members of Congress generate higher revenue overall, which we identify by comparing revenues generated by individuals who narrowly won election to those who narrowly lost. These findings help characterize when lobbyists with different skillsets prove most valuable and the value added by government experience.